Pengembangan Bahan Ajar IPA SMP Berbasis Literasi Sains Topik Lapisan Bumi Dan Bencana - Rabiatul Adawiyah; Maya Istyadji; Ratna Yulinda (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research was triggered by the lack of scientific literacy content in textbooks used by students at school. Therefore, research was carried out and preparation of science learning materials focused on scientific literacy. The aim of this research is to describe the validity of junior high school science teaching materials based on scientific literacy on the topic of earth layers and disasters, evaluated through assessments from experts. The research approach applied is research and development (R&D) using a modified four-D (4D) model. In this research, there are three validation phases, namely defining, designing, and developing. Respondents in this research and development consisted of three validators who work as academics. The data collected is quantitative in the form of product validation scores from questionnaires. The study results show that the module validity level reaches 90%, with an average validity value of 3.59, without any revisions. Meanwhile, the validity of the scientific literacy module reached 95%, with an average validity value of 3.71, without revision. Hence, it can be concluded that the developed teaching materials meet validity criteria and are suitable for use in the context of the learning process.